Asthma exacerbations among asthmatic children receiving live attenuated versus inactivated influenza vaccines. Issue 20 (9th May 2017) - Ray, G. Thomas; Lewis, Ned; Goddard, Kristin; Ross, Pat; Duffy, Jonathan; DeStefano, Frank; Baxter, Roger; Klein, Nicola P.
Abstract: Objective: To investigate whether there is a difference in the risk of asthma exacerbations between children with pre-existing asthma who receive live attenuated influenza vaccine (LAIV) compared with inactivated influenza vaccine (IIV). Material and methods: We identified IIV and LAIV immunizations occurring between July 1, 2007 and March 31, 2014 among Kaiser Permanente Northern California members aged 2 to <18 years with a history of asthma, and subsequent asthma exacerbations seen in the inpatient or Emergency Department (ED) setting. We calculated the ratio of the odds (OR) of an exacerbation being in the risk interval (1–14 days) versus the comparison interval (29–42 days) following immunization, separately for LAIV and IIV, and then examined whether the OR differed between children receiving LAIV and those receiving IIV ("difference-in-differences"). Results: Among 387, 633 immunizations, 85% were IIV and 15% were LAIV. Children getting LAIV vs. IIV were less likely to have "current or recent, persistent" asthma (25% vs. 47%), and more likely to have "remote history" of asthma (47% vs. 25%). Among IIV-vaccinated asthmatic children, the OR of an inpatient/ED asthma exacerbation was 0.97 (95% CI: 0.82–1.15). Among LAIV-vaccinated asthmatic children the OR was 0.38 (95% CI: 0.17–0.90). In the difference-in-differences analysis, the odds of asthma exacerbation following LAIV were less than IIV (Ratio of ORs: 0.40, CI: 0.17–0.95, p value: 0.04). Conclusion: Among children ≥2 years old with asthma, we found no increased risk of asthma exacerbation following LAIV or IIV, and a decreased risk following LAIV compared to IIV.